The Effect of Industrial Work Practices, Career Guidance, and Family Environment on Working Readiness through Soft Skills - Royani, Ida; Rusdarti, Rusdarti; Yulianto, Arief (Journal of Economic Education, 2021)
Vocational High School (SMK) is a formal education which provides a special training pattern to direct their students become the graduates who are ready to enter participate professionally in the business world or even companies. Consequently, the vocational school required to be able to produce graduates with the standard competencies expected by the working world. The aim of this study is to analyze the influence of industrial work practice, career guidance and family environment on working readiness by soft skills. Method of the study used was a quantitative study. The population in this study was all of the students on grade 12th of SMK Negeri 2 and SMK Negeri 9 in Semarang which were 634 students with 139 students as the sample of the study. Data collection technique was questionnaires. The data analysis technique used was a descriptive percentage statistics, path analysis and Sobel test. Results of the study showed that there is an influence of industrial work practice, career guidance, family environment, and soft skills on working readiness. Based on the sobel test result, soft skills can mediate the influence of industrial work practice, career guidance and family environment on working readiness